Advancements in Dam Surveillance Instrumentation: Integrating Monitoring Technologies for Enhanced Safety and Risk Management - ILMI, ABU (Journal of Sustainable Infrastructure, 2025)
This paper explores the advancements in dam surveillance instrumentation, with a focus on integrating monitoring technologies to enhance dam safety and risk management. As climate change, aging infrastructure, and environmental factors increase the vulnerability of dams, there is a growing need for effective surveillance systems to detect potential risks and prevent catastrophic failures. The paper reviews the role of key monitoring technologies, including Structural Health Monitoring (SHM), geotechnical instrumentation, remote sensing, and data acquisition systems, in ensuring the structural integrity of dams. The integration of real-time data monitoring with predictive analytics is highlighted as a key advancement in improving dam safety and operational efficiency. Furthermore, the paper discusses the feasibility and challenges of implementing these technologies in both developed and developing regions, providing valuable insights into their practical application. Finally, the paper identifies future research directions, including the integration of emerging technologies such as AI, machine learning, and blockchain for secure data sharing, to further enhance the capabilities of dam surveillance systems